THE EFFECT OF MARINATION WITH RED GINGER (Zingiber officinale Rosc.) ON CHEMICAL AND HEDONIC QUALITY OF DRIED BEEF - Dwiloka, Bambang; Prasasti, Rahel Nathania Prasasti; Nurwantoro, Nurwantoro (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2024)
Red ginger (Zingiber officinale Rosc.) is a commonly utilized spice plant in blends and marinades. The research was conducted to determine the effect of different red ginger blend concentrations on fat levels, protein levels, antioxidant activity, and hedonic quality of dried beef. The research used a Randomized Block Design and descriptive analysis. Treatments were differentiated by adding different concentrations of red ginger blend (P0 = 0%, P1 = 5%, P2 = 10%, P3 = 15%, and P4 = 20%). The addition of a 15% red ginger blend is the best treatment for the chemical properties of dried beef, while the addition of a 5% red ginger blend is the best treatment for the hedonic properties of dried beef.